KETELADANAN GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR AL-QUR'AN SISWA DI PONDOK PESANTREN AL-ISLAM - Muhammad Haris; Didik Tamamul Iman (STKIP Pesisir Selatan, 2026)
This study aims to analyze the manifestations of exemplary behavior among Islamic Religious Education (IRE) teachers in Quran instruction and its impact on the transformation of students’ learning motivation at the Al-Islam Islamic Boarding School. The study employs a qualitative approach with a case study design to gain an in-depth understanding of the phenomenon within the natural context of the boarding school. Data was collected through participatory observation, in-depth interviews, and documentary analysis, and was subsequently analyzed interactively through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that teachers’ exemplary behavior manifests in three main dimensions: religious discipline, quality of Quranic literacy (fashahah and tajwid), and moral integrity in pedagogical interactions. This exemplary behavior functions as a living curriculum that shapes the process of value identification and internalization within the students. The findings also reveal a shift in learning motivation from an extrinsic orientation toward a more autonomous and reflective intrinsic motivation. This transformation is indicated by increased self-initiated learning, consistent independent revision (muraja’ah), and deeper emotional engagement in memorization activities.This study concludes that teacher exemplary behavior is a transformative foundation in building sustainable motivation for learning the Qur’an, thus requiring systemic support among Islamic boarding schools, families, and the strengthening of digital literacy.